Refinement Equations and Feller Operators - Morawiec, Janusz; Kapica, Rafał (Integral equations and operator theory, 2011)
Results on the existence and non-existence of nontrivial -solutions of the refinement equation are obtained by considering fixed points a Feller operator acting on measures associated with this equation.